2011
DOI: 10.1007/978-3-642-20807-2_6
|View full text |Cite
|
Sign up to set email alerts
|

TSP on Cubic and Subcubic Graphs

Abstract: Abstract. We study the Travelling Salesman Problem (TSP) on the metric completion of cubic and subcubic graphs, which is known to be NP-hard. The problem is of interest because of its relation to the famous 4/3 conjecture for metric TSP, which says that the integrality gap, i.e., the worst case ratio between the optimal values of the TSP and its linear programming relaxation, is 4/3. Using polyhedral techniques in an interesting way, we obtain a polynomial-time 4/3-approximation algorithm for this problem on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…While Christofides' algorithm [6] gives a 3 2 approximation even for graph-TSP, a small but constant improvement was presented by Oveis-Gharan et al [17]. Mömke and Svensson [14] improved this significantly while further improvements by Sebö and Vygen [18] have brought the current best approximation factor for graph-TSP down to Another line of work has focused on graph theoretic methods to obtain improved approximation factors: Boyd et al [5] showed a 4 3 approximation for 2-connected cubic graphs; Correa et al [7] gave an algorithm that finds a tour of length at most ( )n in n-node 2-connected cubic graphs, while Karp and Ravi [12] gave an algorithm that finds a tour of length at most 9n 7 in cubic bipartite graphs. For general, d-regular connected graphs, Vishnoi [19] gave an algorithm for finding tours of length at most…”
Section: Related Workmentioning
confidence: 99%
“…While Christofides' algorithm [6] gives a 3 2 approximation even for graph-TSP, a small but constant improvement was presented by Oveis-Gharan et al [17]. Mömke and Svensson [14] improved this significantly while further improvements by Sebö and Vygen [18] have brought the current best approximation factor for graph-TSP down to Another line of work has focused on graph theoretic methods to obtain improved approximation factors: Boyd et al [5] showed a 4 3 approximation for 2-connected cubic graphs; Correa et al [7] gave an algorithm that finds a tour of length at most ( )n in n-node 2-connected cubic graphs, while Karp and Ravi [12] gave an algorithm that finds a tour of length at most 9n 7 in cubic bipartite graphs. For general, d-regular connected graphs, Vishnoi [19] gave an algorithm for finding tours of length at most…”
Section: Related Workmentioning
confidence: 99%
“…In [14] there is an unproven claim that (1,2)-TSP is APX-hard when the graph of edges of length 1 is cubic, which would imply APXhardness of graph-TSP on cubic graphs. Also note that the 3/2-ratio of Christofides' algorithm is tight for cubic graph-TSP (see [11]). …”
Section: Conjecture 1 For the Metric Tsp The Integrality Gap α(Tsp) mentioning
confidence: 99%
“…Shortly after, improvements for graph-TSP were obtained independently by Aggarwal et al [1], Oveis Gharan et al [30] and by us [10,11]. Aggarwal et al gave a 4/3-approximation for 3-edge-connected cubic graphs by constructing a TSP tour of length at most 4n/3 − 2 when n ≥ 6.…”
Section: Conjecture 1 For the Metric Tsp The Integrality Gap α(Tsp) mentioning
confidence: 99%
See 1 more Smart Citation
“…This general approach was also taken by Boyd et al who combined it with polyhedral ideas to obtain approximation guarantees of 4/3 for cubic graphs and 7/5 for subcubic graphs, i.e. graphs with degree at most three at each vertex [BSvdSS11]. Shortly afterwards, Oveis Gharan et al proved that a subtle modification of Christofides' algorithm has an approximation guarantee of 3/2 − ǫ 0 for graph-TSP on general graphs, where ǫ 0 is a fixed constant with value approximately 10 −12 [GSS11].…”
Section: Recent Progress On Graph-tspmentioning
confidence: 99%